Identification and optimization of lemongrass essential oils extracted by hydrodistillation and microwave assisted hydrodistillation methods - Ranitha, Mathialagan (2014)
The use of plant extracts in different commercial sectors such as pharmaceutical, food and chemical industries has gained renewed attention in the last few decades. Existing conventional extraction methods are known for their economic impact due to high energy, toxic solvents, time consumption as well as causing environmental impact by releasing CO2 and untreatable waste. Thus, microwave technique has been developed recently for extraction of natural products from plant materials due to the need of a rapid, safe and cost effective method in this field. Current study has been carried out to investigate the efficiency of microwave assisted hydrodistillation (MAHD) over conventional hydrodistillation (HD) for the extraction of essential oils from Lemongrass (Cymbopogon citratus). The oil extraction process was based on three major operating parameters namely the water to plant material ratio, microwave power level and extraction time and their interaction has been evaluated by using one-factor-at-a-time experiments (OFAT). In comparison of both extraction techniques, MAHD resulted in shorter extraction time to obtain optimum yield of 1.464% which was about 90 min compare to 150 min in HD. The results from OFAT experiments were being analyzed in optimization study of MAHD system using Response Surface Methodology (RSM) based on central composite design (CCD). All considered factors were statistically significant for extraction efficiency, while the most important factor was water to plant material ratio. Water to plant material ratio of 8:1, microwave power level of 250W and extraction time of 90 min were determined as the optimal parameter configuration with yield of 1.461%. This proved the experimental value was in good agreement with predicted model value. Besides, this optimum parameters condition was also being used for qualitative analysis to determine the chemical composition of Lemongrass oil by Gas chromatography-mass spectrometry (GC-MS) analysis in order to study the effects of extraction method and extraction time on chemical composition. As a result, more than 34 constituents were being identified. Five key compounds were present in all the extracts of both methods and they were neral, geranial, β-myrcene, geraniol and linalool. MAHD extract seems to contain higher amount of oxygenated compound. The oil obtained under optimized condition of both methods was selected for cytotoxicity study using brine shrimp lethality (BLT) assay. The results shows HD extracts, with higher β-myrcene content, was more toxic than the one obtained by MAHD with LC50 value of 13ppm and 18ppm respectively. To attain qualitative understanding of microwave extraction process, temperature analysis was being carried out to perform heat generation calculation. It shows the volume rate of heat generation decreasing within irradiation time due to the decreasing of dielectric properties. The evaluation on cost, energy and environmental impact by MAHD and HD shows the conventional method utilizes three time higher energy compared to the recent technique. Due to the substantial saving of time, cost and energy with no significant changes in its constituents, MAHD process found to be a good alternative green technology to conventional methods. Results obtained in this study have exposed the capability of MAHD techniques as another promising method for extraction of essential oils. Further works are nevertheless required to provide deeper understanding of the mechanism involved to facilitate the development of an optimum system applicable to the industry.